The Phanerozoic development of the Kangerdlugssuaq area, East Greenland - Brooks, Charles Kent; Nielsen, Troels F. D. (Meddelelser om Grønland. Geoscience, 1982)
This paper presents an up-to-date description of the state of knowledge on the post-Precambrian geology of the Kangerdlugssuaq area, which is a key area for theearly stages of continental break-up in the North Atlantic. The area is analogous to present-day Iceland but differs from Iceland in that continental crust is present and the erosional level is deeper. The area was affected by the Caledonian orogeny as revealed by the Batbjerg intrusion, which contains screens of Palaeozoic limestones and unique potassic rocks which relate it to the Assynt Province of Scotland. Basin formation in the early Cretaceous heralded a period of sedimentation and volcanism which formed deposits several kilometres in thickness. The basalts are believed to have been extruded just prior to anomaly 24 (i.e. 55 - 53 m.y. ago) which reaches the coast just north of this area. The basalts are overwhelmingly tholeiites of "plume" type and include picrites. They may be derived from two different mantle sources. Layered gabbroic intrusions which are penecontemporaneous with the basalts are widespread in the area and a number of ultramafic plugs also occur. Syenites, both under- and oversaturated, are the most voluminous rock types of the area at the present erosional level and are somewhat later. The syenites show abundant signs of contamination with the country rocks. The Gardiner complex is the eroded core of a nephelinitic volcano and contains melilite rocks and carbonatites. Related nephelinitic lavas are found in inland areas. In the area many dike swarms are recognized which vary from tholeiitic to strongly alkaline suites emplaced between ca. 55 and 35 m.y. ago and which give good evidenceof the magmatic and chronological development of the area. Tertiary tectonism includes three main elements: the well known coastal flexure, amajor dome centred on Kangerdlugssuaq and regional plateau uplift.